Assessing the role of anastomotic level in low anterior resection (LAR) surgery among rectal cancer patients in the development of LAR syndrome: a systematic review study - Mohammad Reza Hashempour; Muhammadhosein Moradi; Reza Ghasemian oroomi; Siamak Daneshvar; Alipasha Meysamie; Mohammadreza Nikshoar; Fakhrosadat Anaraki (BMC Surgery, 2023)
Abstract Background The etiology of LARS has not been elaborated on clearly. Studies have reported neoadjuvant therapy, low-lying rectal cancers, adjuvant therapy and anastomotic leakage as risk factors for the development of LARS. Anastomotic level has also been proposed as a possible risk factor; However, there have been conflicting results. This study aims to evaluate the role of the level of anastomosis as a potential risk factor for the development of LARS. Method A systematic literature search was conducted on Pubmed, Scopus, Embase, and Web of Science databases using Mesh terms and non-Mesh terms from 2012 to 2023. Original English studies conducted on rectal cancer patients reporting of anastomotic level and LARS status were included in this study. Eligible studies were assessed regarding quality control with Joanna-Briggs Institute (JBI) questionnaires. Results A total of 396 articles were found using the research queries, and after applying selection criteria 4 articles were selected. A sample population of 808 patients were included in this study with a mean age of 61.51 years with male patients consisting 59.28% of the cases. The Mean assessment time was 15.6 months which revealed a mean prevalence of 48.89% for LAR syndrome. Regression analysis revealed significantly increased risk of LAR syndrome development due to low anastomosis level in all 4 studies with odds ratios of 5.336 (95% CI:3.197–8.907), 3.76 (95% CI: 1.34–10.61), 1.145 (95% CI: 1.141–2.149) and 2.11 (95% CI: 1.05–4.27) for low anastomoses and 4.34 (95% CI: 1.05–18.04) for ultralow anastomoses. Conclusions LARS is a long-term complication following surgery, leading to reduced quality of life. Low anastomosis level has been reported as a possible risk factor. All of the studies in this systematic review were associated with an increased risk of LARS development among patients with low anastomosis.